English Teachers' Challenges in The Implementation of 2013 Curriculum in Vocational High Schools of Agriculture in South Kalimantan - Muhammad Ali Usman; Sintha Tresnadewi (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This study is intended to describe challenges faced by English teachers in the Vocational High Schools of Agriculture during the implementation of 2013 Curriculum. This study used descriptive qualitative research design which was conducted at two Vocational High Schools of Agriculture in South Kalimantan. The result was devided into five items based on the research questions. The first was challenges in designing lesson plan. The second was challenges in the lesson implementation. The third was challenges in the learning assessment. The fourth was challenges in the classroom management practice. The last finding dealt with the implementation of professional development strategy. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan tantangan-tantangan yang dihadapi oleh guru bahasa Inggris di SMK Pertanian selama implementasi Kurikulum 2013. Penelitian ini menggunakan desain kualitatif deskriptif yang dilaksanakan pada dua SMK Pertanian di Kalimanta Selatan. Hasil dari penelitian ini dibagi menjadi lima al berdasarkan pertanyaan penelitian. Pertama, tantangan-tantangan dalam penyusunan RPP. Kedua, tantangan-tantangan di dalam pelaksanaan pembelajaran. Ketiga, tantangan dalam evaluasi pembelajaran. Keempat, tantangan-tantangan dalam melaksanakan praktik manajemen kelas. Kelima, berkaitan dengan pelaksanaan strategi pengembangan profesionalisme guru.